Tribological Behavior of Polyethylene/Light Metal Pairs in Low Viscosity Organic Solvents - Yuko Hibi; Koji Miyake (Tribology Online, 2018)
Sliding tests with a polyethylene (PE) pin against aluminum (Al) and titanium (Ti) disks were conducted under dry conditions, in n-undecane and in ethanol using a unidirectional pin-on-disk machine to evaluate lubrication compatibility. Compared to the dry condition, n-undecane lubrication reduced friction of both the PE pin/Al disk pair and PE pin/Ti disk pair and increased the wear of the tested materials other than PE pin slid against Ti disk. Ethanol lubrication reduced friction and wear of the PE pin/Ti disk pair but increased those of the PE pin/Al disk pair. In all environments tested, the wear of the PE pin/Ti disk pair was lower than that of PE pin/Al disk pair. Profile measurements of the wear tracks on the disks, microstructural observation and chemical analysis of the worn surfaces were performed. The results suggest that the tribological behavior was influenced by the abrasive wear resistance of the metal, the permeability of the solvent into PE, chemical reactivity of the solvent and the thermal conductivity of the metal.